THE ASSESSMENT OF MOTOR SKILLS AND PHYSICAL DEVELOPMENT TO A NUMBER OF STUDENTS IN THE MOLDOVA AREA - Ionuț ONOSE; Raluca Mihaela HODORCĂ; Adriana ALBU (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2018)
Growth and development are two processes influenced by the action of internal and external factors. Differences in physical development and motor skills may occur depending on the geographical area. Material and Methods: The study is conducted on a lot of 100 pupils from 5th grade, from schools from 3 counties of Moldova (Iasi, Vrancea, Suceava). Physical development and motor skills have been appreciated. Results and discussions: Harmonic development is present in 55 students, with insignificant differences on collectives. Motor skills rated at 10 are only present in 25 students, but young people in Suceava County are distinguished by the existence of a small number of cases reaching this level. The calculated differences are statistically significant. Conclusions: Motor abilities may vary depending on the geographic region, which is important for the orientation of young people towards sport performances.